Iraq Crude Oil Exports – April, May, June/ 2020 - SOMO, Ministry of Oil - Oil Marketing Company (Journal of Petroleum Research and Studies, 2022)
Table 1. Iraq Crude Oil Exports – April 2020 Table 2. Iraq Crude Oil Exports – May 2020 Table 3. Iraq Crude Oil Exports – June 2020